Oncolytic viruses combined with immune checkpoint therapy for colorectal cancer is a promising treatment option - Ren, Yi; Miao, Jia-Meng; Wang, Yuan-Yuan; Fan, Zheng; Kong, Xian-Bin; Yang, Long; Cheng, Gong (Frontiers in Immunology, 2022)
Immunotherapy is one of the promising strategies in the treatment of oncology. Immune checkpoint inhibitors, as a type of immunotherapy, have no significant efficacy in the clinical treatment of patients with pMMR/MSS/MSI-L mCRC alone. Therefore, there is an urgent need to find combination therapies that can improve the response rate of immune checkpoint inhibitors. Oncolytic viruses are a new class of cancer drugs that, in addition to directly lysing tumor cells, can facilitate the action of immune checkpoint inhibitors by modulating the tumor microenvironment and transforming “cold” tumors into “hot” ones. The combination of oncolytic viruses and immune checkpoint inhibitors is currently being used in several primary and clinical studies to treat tumors with exciting results. The combination of genetically modified “armed” OV with ICIs is expected to be one of the treatment options for pMMR/MSS/MSI-L mCRC. In this paper, we will analyze the current status of oncolytic viruses and ICIs available for the treatment of CRC. The feasibility of OV in combination with ICI for CRC will be discussed in terms of the mechanism of action of OV in treating tumors.